T-3262 URINARY TRACT INFECTION - KAWASHITA, EISO; SANDA, NORIAKI; NAGAOKA, SYUJI; SEO, KAZUSHI; NAKANO, HIROSHI; HAYASHI, MUTSUO; NIHIRA, HIROMI (CHEMOTHERAPY, 1988)
The clinical efficacy of T-3262, a new pyridone-carboxylic acid derivative, was studied in genitourinary tract infections. T-3262 was administered orally at a dose of 75-150 mg 2 or 3 times per day for 3-14 days to 33 patients (6 acute uncomplicated cystitis, 25 complicated urinary tract infection and 2 acute urethritis), and the following results were obtained. 1) Using the criteria proposed by the Japanese UTI Committee, the clinical efficacy rate was 100% in acute uncomplicated cystitis and 90% in complicated urinary tract infection. 2) The clinical efficacy rate by doctor's evaluation was 100% in acute uncomplicated cystitis, 75% in complicated urinary tract infection and 100% in acute urethritis. 3) Bacteriologically, 5 of 5 strains were eradicated in acute uncomplicated cystitis and 22 of 23 were eradicated in complicated urinary tract infections. 4) Side effects observed were nausea and diarrhea in one case and stomach distress in another. They disappeared in a few days after discontinuance of T-3262, and no abnormal laboratory data were observed